Tebuconazole and terbuthylazine encapsulated in nanocarriers: preparation, characterization and release kinetics - Lopez-Cabeza, Rocio; Kah, Melanie; Grillo, Renato [UNESP]; Koutny, Marek; Salac, Jan; Bilkova, Zuzana; Eghbalinejad, Mahleh; Hofman, Jakub (Royal Soc Chemistry, 2022)
In this work, tebuconazole and terbuthylazine were encapsulated in nanocarriers prepared from the polymers poly-epsilon-caprolactone, poly(3-hydroxybutyrate) and poly(acrylic acid)/polylactide, and in a nanostructured lipid carrier. The release kinetics of the prepared nanoformulations was assessed by the dialysis method and the results obtained from these release experiments were related to the durability of the nanoformulations. The outcomes suggested that the release of the active ingredients in these nanoformulations depended mainly on the interaction between the nanocarrier materials and the pesticides. In addition, it was found that the durability of the complex formed by tebuconazole encapsulated in poly(3-hydroxybutyrate) was affected by its dilution, the durability being shorter with the increase of dilution factor. The findings in this work could help the design of pesticide nanoformulations with certain durability according to the pesticide doses required in the field by selecting the appropriate nanocarrier material. Likewise, the results indicate the need to evaluate the release kinetics of the active ingredients under dilution of the nanoformulations, since the dilution in the mixing tank before application or in the soil during irrigation or rainfall events could influence the durability of the nanoformulations and as a consequence, their environmental risk assessment.